Religious education and the concept of universal fraternity in the light of the encyclical Fratelli tutti of Pope Francis - Rybicki, Adam (Teaching theology and religion, 2022)
In the face of growing tensions between nations, communities, and individuals, it is necessary to build understanding and dialog between them. Political, economic, and cultural activities are not always sufficient and effective, due to the fact that attitudes toward other people depend less on systemic solutions, laws, and procedures than on what is inside human beings, their empathy and solidarity. Pope Francis has therefore proposed a platform for understanding and peace-building between people that relates to people's interior development, that is, the idea of universal fraternity. This term, used after Pope Francis, is understood as fraternity of both men and women, brothers and sisters. The article analyzes this concept and indicates how religious education in a broad sense can contribute to the promotion of this idea. The problem hereof can be expressed in the questions: How to understand the idea of universal fraternity, how to realize that we are all sisters and brothers, what concrete fruits could the realization of this idea bring? What role does religious education play in acceptance and understanding, and then implementation as well as promotion of this idea that cannot be reduced to the transmission of knowledge alone?